Diminished B cell secretory capacity in patients with noninsulin-dependent diabetes mellitus. - Ward, W K (1984)
In order to assess whether patients with noninsulin-dependent diabetes mellitus (NIDDM) possess normal insulin secretory capacity, maximal B cell responsiveness to the potentiating effects of glucose was estimated in eight untreated patients with NIDDM and in eight nondiabetic controls. The acute insulin response to 5 g intravenous arginine was measured at five matched plasma glucose levels that ranged from approximately 100-615 mg/dl. The upper asymptote approached by acute insulin responses (AIRmax) and the plasma glucose concentration at half-maximal responsiveness (PG50) were estimated using nonlinear regression to fit a modification of the Michaelis-Menten equation. In addition, glucagon responses to arginine were measured at these same glucose levels to compare maximal A cell suppression by hyperglycemia in diabetics and controls. Insulin responses to arginine were lower in diabetics than in controls at all matched glucose levels (P less than 0.001 at all levels). In addition, estimated AIRmax was much lower in diabetics than in controls (83 +/- 21 vs. 450 +/- 93 microU/ml, P less than 0.01). In contrast, PG50 was similar in diabetics and controls (234 +/- 28 vs. 197 +/- 20 mg/dl, P equals NS) and insulin responses in both groups approached or attained maxima at a glucose level of approximately 460 mg/dl. Acute glucagon responses to arginine in patients with NIDDM were significantly higher than responses in controls at all glucose levels. In addition, although glucagon responses in control subjects reached a minimum at a glucose level of approximately 460 mg/dl, responses in diabetics declined continuously throughout the glucose range and did not reach a minimum. Thus, A cell sensitivity to changes in glucose level may be diminished in patients with NIDDM. In summary, patients with NIDDM possess markedly decreased maximal insulin responsiveness to the potentiating effects of glucose. Such a defect indicates the presence of a reduced B cell secretory capacity and suggests a marked generalized impairment of B cell function in patients with NIDDM.